Delayed diagnosis and treatment of a psoas abscess as a link between spondylodiscitis and septic necrosis of the femoral head: a case report - Scaglia, Marco; Lugani , Giovanni; Cassini , Marco; Ambrosini , Carlo; Magnan , Bruno (Acta Biomedica Atenei Parmensis, 2020)
Background: Infections of the spine and hip joint are not common and, as described in literature, they are occasionally linked by a psoas abscess. In patients suffering back pain with history of spondylodiscitis, the spine as primary source of infection for a secondary psoas abscess should always be included in differential diagnosis. A delay in diagnosis of the psoas abscess could lead to septic femoral head necrosis. Case report: A case of a 65-year-old woman affected by septic femoral head necrosis due to spondylodiscitis and secondary psoas abscess is reported; the patient needed a specific antibiotic therapy then undergoing a total hip arthroplasty(THA). Discussion and conclusion: Diagnoses of lumbar spine infection and psoas abscess are difficultand often delayed. Since the symptoms of both are non-specific, high degree of suspicious is necessary. In psoas abscess, an early diagnosis is important, because a delayed treatment could result in septic femoral head necrosis requiring both a prolonged antibiotic therapy and a THA.